"نمذجة تقلبات عوائد مؤشرات الأسواق المالية - دراسة حالة سوق المالي السعودي 2012-2022- " - بشير, نسيب; عمار, لبيض; لخضر, تريكي (unuversity of eloued- جامعة الوادي, 2023)
" تهدف الدراسة إلى التنبؤ بتقلبات عوائد الأسواق المالية السعودية خلال الفترة (2012/ 2022) وذلك باستخدام بيانات أسبوعية تمتد من الأسبوع الأول 2012/01/04 وتنتهي في الأسبوع الأخير 2022/12/25. حيث قمنا بدراسة سلوك عوائد تقلبات السوق المالي السعودي وبذلك بالاعتماد على نموذج GARCH حيث توصلنا من خلال هذه الدراسة غلى أنه يمكن لنموذج GARCH أن يقدم أفضل تنبؤ لتقلبات عوائد السوق المالي السعودي " "The study aims to predict the fluctuations in the returns of the Saudi financial markets during the period (2012/2022) using weekly data that extends from the first week 01/04/2012 and ends in the last week 12/25/2022. Where we studied the behavior of the returns of the fluctuations of the Saudi financial market، and thus based on the GARCH model، where we concluded through this study that the GARCH model can provide the best prediction of the fluctuations of the returns of the Saudi financial market. "
Keywords: عوائد، تقلبات، تداول، مؤشر، سوق مالي.; Returns، volatility، trading، index، financial market.